2014
DOI: 10.1021/nl5033205
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Alternating Binary Polymer Nanodroplet Array by Sequential Spin Dewetting

Abstract: We report a facile technique for fabricating an ordered array of nearly equal-sized mesoscale polymer droplets of two constituent polymers (polystyrene, PS and poly(methyl methacrylate), PMMA) arranged in an alternating manner on a topographically patterned substrate. The self-organized array of binary polymers is realized by sequential spin dewetting. First, a dilute solution of PMMA is spin-dewetted on a patterned substrate, resulting in an array of isolated PMMA droplets arranged along the substrate grooves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 49 publications
0
51
0
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The template-directed and template-assisted dewetting of the thin polymer bilayer have been investigated extensively due to their technological and scientic importance. [31][32][33][34][35] Mukherjee et al 32,33 reported the dewetting process of a thin bilayer of polystyrene and poly(methylmethacrylate) on a topographically patterned nonwettable substrate, and using this method they fabricate many different structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The template-directed and template-assisted dewetting of the thin polymer bilayer have been investigated extensively due to their technological and scientic importance. [31][32][33][34][35] Mukherjee et al 32,33 reported the dewetting process of a thin bilayer of polystyrene and poly(methylmethacrylate) on a topographically patterned nonwettable substrate, and using this method they fabricate many different structures.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [10][11][12][13][14][31][32][33][34][35] on the template-directed or template-assisted dewetting of the thin polymer lms mainly focus on the inuence of the geometry and size of the template pattern on the dewetting structures. In this paper, we concentrate on the inuence of instability mode on the templateassisted dewetting process of the thin polymer bilayer.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the past decades, enormous experimental and theoretical endeavors have been made to improve the ordering degree of the dewetting-induced features. 9−12,14−28 Previously, three preferred strategies have been introduced for directing dewetting: chemically 14,15 or topographically patterned substrates [9][10][11][20][21][22][23][24][25]28 or externally structured templates. 16 −19 In the above directed dewetting, lithography-based techniques such as photolithography or e-beam etching have been directly or indirectly involved in the fabrication of the required patterned substrates and structured templates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thin polymer film can become unstable and spontaneously rupture whenever the intermolecular disjoining pressure increases with increased film thickness [6][7][8][9][10][11][12][13][14][15][16][17] . The dewetting of thin polymer film progresses with the formation and growth of randomly placed holes with a certain mean length scale.…”
Section: Introductionmentioning
confidence: 99%